Readiness of National Industries Infrastructure to Support the RDE Programme in Indonesia - Dharu Dewi; Arief Tris Yuliyanto; Moch Djoko Birmano; Rr Arum Puni; Rijanti Rijanti; Mudjiono Mudjiono; Taswanda Taryo; Susyadi Susyadi; Rustama Rustama; Sriyana Sriyana (Journal of Applied Sciences and Advanced Technology, 2020)
Nuclear Power Plant (PLTN) is one of the options to meet electricity for society and industry. BATAN has developed an Experimental Power Reactor (RDE) design which is one type of Non-Commercial Power Reactor (RDE) is a HTGR (High Temperature Gas-cooled Reactor) NPP with 10 MWth Pebble Bed Reactor (PBR) technology, and is used for non-electric electricity. This reactor type can generate electricity and heat. The development of RDE in Indonesia requires 19 aspects of nuclear infrastructure. One aspect of them is the involvement of national industries. The RDE development is expected to involve several national industries that can participate in supplying government goods and services. The purpose of this research is to determine the capability and readiness of the national industrial infrastructure to be able to participate in the development of RDE in Indonesia. The methodology used is literature review, technical surveys or visits, and technical consultations with key persons from industries. The study results conclude that the civil construction industries and the EPC industries have the readiness and ability to be able to build RDE building especially for non-nuclear parts. The Architect Engineering have the potential and capability for the RDE project management, engineering and Design development. The mechanical industries have the potential and capability to produce turbines, generators, condensers and heat exchangers. The electrical industries have the potential and capability to supply electrical components for the electrical system, such as Switchgear, main transformers, distribution transformers, generators, conductors, power cables, connectors and electrical panels. The Instrumentation & Control industries have the potency and capability to supply I&C products such as instrumentation cable, instrumentation communication system, temperature controller, etc. The output expected from this research is the readiness of nuclear infrastructure, especially the national industries for the supply of non-nuclear components.